2006
DOI: 10.1007/s10182-006-0241-1
|View full text |Cite
|
Sign up to set email alerts
|

Power kurtosis transformations: Definition, properties and ordering

Abstract: Power kurtosis transformation, leptokurtosis, kurtosis ordering, JEL C16, C51,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The branch length and radius data for the whorl-level analysis were log-transformed. The data for the branch-level analysis were subjected to an optimizing (iterated) Box-Cox transformation, followed by a monotonic, inverse-errorfunction correction to mitigate negative kurtosis caused by excessive tail compression by the Box-Cox transformation (Klein and Fischer, 2006). All transformed data beyond four standard deviations about the mean were excluded from the analyses (<0.1% of the total datasets).…”
Section: Discussionmentioning
confidence: 99%
“…The branch length and radius data for the whorl-level analysis were log-transformed. The data for the branch-level analysis were subjected to an optimizing (iterated) Box-Cox transformation, followed by a monotonic, inverse-errorfunction correction to mitigate negative kurtosis caused by excessive tail compression by the Box-Cox transformation (Klein and Fischer, 2006). All transformed data beyond four standard deviations about the mean were excluded from the analyses (<0.1% of the total datasets).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Klein and Fischer (2006) showed that the parameter γ can also be interpreted as a skewness parameter in terms of the partial ordering proposed by van Zwet (1964). This reparameterisation can also be used in DTP distributions for inducing orthogonality between σ and γ through parameterisations that satisfy a(γ) + b(γ) = constant.…”
Section: Reparameterisationsmentioning
confidence: 94%
“…Some examples of skewing mechanisms can be found in Azzalini (1985) and Fernández and Steel (1998a). Examples of elongations can be found in Hoaglin et al (1985), Haynes et al (1997), Fischer and Klein (2004), and Klein and Fischer (2006). A third class of transformations consists of those that contain two parameters that are used for modelling skewness and kurtosis jointly.…”
Section: Introductionmentioning
confidence: 99%